Thermal and decay-resistance properties of tropical wood–plastic composites - Md Saiful, Islam; Sinin, Hamdan; Habibur Rahman, Sobuz; Md Rezaur, Rahman; Abu Saleh, Ahmed (SAGE, 2012)
This investigation concerns about the thermal and decay resistance properties of tropical wood polymer composites. Wood polymer composites were prepared from several types of tropical wood species by impregnating the woods with ethyl methacrylate that was combined with a cross-linker, hexamethylene diisocyanate. Thermal properties of wood polymer composites in terms of thermogravimetric analysis and differential scanning calorimetry were evaluated, and an improvement in thermal stability was found on ethyl methacrylate and ethyl methacrylate–hexamethylene diisocyanate treatment. A significant improvement in decay resistance was also identified in wood polymer composites that were treated with ethyl methacrylate, and also, with ethyl methacrylate–hexamethylene diisocyanate. The improvement in properties was observed as more potential with ethyl methacrylate–hexamethylene diisocyanate combination rather than ethyl methacrylate.